Effects of milk replacer feeding level on growth performance, rumen development and the ruminal bacterial community in lambs - Huang, Yongliang; Wang, Guoxiu; Zhang, Qian; Chen, Zhanyu; Li, Chong; Wang, Weimin; Zhang, Xiaoxue; Wang, Xiaojuan; Zhang, Deyin; Cui, Panpan; Ma, Zongwu (Frontiers in Microbiology, 2023)
Feeding with a suitable level of milk replacer (MR) can improve the survival rate and stimulate the growth potential of early lambs. However, feeding excessive MR might be detrimental to rumen development and microbial colonization. Herein, we investigated the effects of feeding different levels of MR on rumen digestive function and ruminal microorganisms. Fourteen healthy male Hu lambs with similar birth weights and detailed pedigree records were divided into two groups to receive low (2% of average body weight per day) and high (4% of average body weight per day) levels of MR. We analyzed the effects of the MR feeding level on growth performance, fiber degradation rates, rumen fermentation parameters, enzyme activities and rumen histomorphology. We found that feeding with a high level of MR improved the average daily gain of early lambs, but decreased the starter intake, rumen weight and papillae length. We also analyzed the effects of the MR feeding level on the rumen microbiota using 16S-rRNA amplicon sequencing data. The results showed that high a MR feeding level increased the rumen microbial diversity but decreased the abundance of many carbohydrate degrading bacteria. Several bacterial genera with significant differences correlated positively with rumen cellulase activity and the acid detergent fiber degradation rate. Our results suggested that a high level of MR could improve the growth performance of early lambs in the short term; however, in the long term, it would be detrimental to rumen development and have adverse effects on the adaptation process of the microbiota to solid feed.